2023
DOI: 10.1002/ppp3.10364
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the perceived societal benefits of and threats from trees for the delivery of livelihoods and community development

Abstract: Societal Impact Statement Understanding the perceptions of benefits and threats from trees is important for the livelihoods of communities. The study used focus group discussions, key informant interviews, and a questionnaire survey of 226 households in the province of KwaZulu‐Natal, South Africa. The findings showed that household socio‐economic factors such as gender and land tenure influenced perceptions of tree growing, and households that were involved in a tree restoration project viewed trees as contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Redundancy analysis revealed that wealthier households often disagreed or strongly disagreed with the socioecological benefts of agroforestry, suggesting that socioeconomic factors may infuence perceptions due to alternative income sources or resource access [72]. However, households with more years of residence in the area strongly agreed with the benefts of agroforestry, likely because of their familiarity with the local environment and experience with agroforestry practices, which may have had positive impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Redundancy analysis revealed that wealthier households often disagreed or strongly disagreed with the socioecological benefts of agroforestry, suggesting that socioeconomic factors may infuence perceptions due to alternative income sources or resource access [72]. However, households with more years of residence in the area strongly agreed with the benefts of agroforestry, likely because of their familiarity with the local environment and experience with agroforestry practices, which may have had positive impacts.…”
Section: Discussionmentioning
confidence: 99%